지역사회 주의력결핍·과잉행동장애 아동의 기질 및 성격 특성 - 조수철(Soo-Churl Cho); 김붕년(Boong-Nyun Kim); 정동선(Dong-Sun Jung); 황준원(Jun-Won Hwang); 신민섭(Min-Sup Shin); 류인균(In-Kyoon Lyoo); 김재원(Jae-Won Kim); 고복자(Bock-Ja Go); 이상은(Sang-Eun Lee); 정선우(Sun-Woo Jung); 김효원(Hyo-Won Kim) (Soa--chʻŏngsonyŏn chŏngsin ŭihak = Journal of child & adolescent psychiatry, 2006)
Objectives : The objective of this study was to evaluate the differences in patterns of temperament and character, as assessed by the Junior Temperament and Character Inventory (JTCI), between the children with attention-deficit/hyperactivity disorder (ADHD) and the control group in a community sample. In addition, we examined the potential differences on JTCI profiles according to the ADHD subtypes. Methods : Parents of 185 ADHD subjects (mean age $9.0{±}1.7$ years), as diagnosed by the DISC-IV, and 185 age- and gender-matched comparison children have completed the parent's version of the JTCI. Results : The ADHD group scored significantly higher in Novelty Seeking and lower in Persistence than the comparison group on JTCI. However, there were no significant differences in the temperament or character profiles by the ADHD subtypes. Conclusion : The results of this study suggest that the temperamental factors of higher Novelty Seeking and lower Persistence are related to ADHD. The temperament or character profiles in this study do not provide support for the distinctiveness of the ADHD subtypes.